The Effect of Metallicity on the AGB Stars Evolution by Using SyntheticModel - Chiad, Behaa; Ali, Nathera; Abdullah, Sundus; Salih, Mohammed (Iraqi Journal of Science, 2024)
Stars whose initial masses are between (0.89 - 8.0) M☉ go through anAsymptotic Giant Branch (AGB) phase at the end of their life. Which have beenevolved from the main sequence phase through Asymptotic Giant Branch (AGB).The calculations were done by adopted Synthetic Model showed the followingresults: 1- Mass loss on the AGB phase consists of two phases for period (P <500)days and for (P>500) days; 2- the mass loss rate exponentially increases with thepulsation periods; 3- The expansion velocity VAGB for our stars are calculatedaccording to the three assumptions; 4- the terminal velocity depends on severalfactors likes metallicity and luminosity. The calculations indicated that a super windphase (S.W) developed on the AGB phases, operates only during the latter part ofthe quiescent phase. The results indicate that the time scale of mass loss depends onthe metallicitiy of stars and mass core.